PENGARUH LOYALITAS KEPADA SUPERVISOR (LOYALTY TO SUPERVISOR) TERHADAP KEPUASAN KERJA (JOB SATISFACTION) DAN INTENT TO STAY - B Medina Nilasari (Universitas Trisakti, 2006)
This study investigates the effect of loyalty to supervisor and job satisfaction and intent to stay. Loyalty to supervisor explained variance two outcomes variable over and above thatexplained by organizational commitment. The hypotheses were tested with a sample of 225 empłoyees in Trisakti University. The results indicate that loyally to supervisor is positively effected to job satisfaction but negatively effected to intent to stay. The results suggested that, in Trisakti Unlversity, the supervisor is an important factor influencing employee attitudes at work.